The evil that men do : a Dorothy Martin mystery - Dams, Jeanne M. (Dams, Jeanne M. Dorothy Martin mysteries, 2011)
Dorothy Martin and her husband, retired Chief Constable Alan Nesbitt, are on holiday in the idyllic English village of Broadway when they stumble across the body of a man who appears to have fallen down a disused quarry. When it is revealed that the man, a local farmer, was probably pushed over the edge, and that the police have failed to find any suspects or motives for the murder, Dorothy can't help but get involved . . .